(untitled) (Indian Journal of Pure & Applied Physics (IJPAP), 2026)
Geomagnetic storms represent significant space weather phenomena with the potential to disrupt critical technological infrastructure, including communication satellites, navigation systems, and terrestrial power grids. This study presents a descriptive analysis of the four most geo-effective geomagnetic storms of Solar Cycle 24 (2008–2019), a cycle noted for its unusually low activity. The heliospheric drivers of these events are investigated by correlating solar and interplanetary data with the disturbance storm time (Dst) index. The analysed storms, including the notable "St. Patrick’s Day" storm of 17 March 2015, as well as events on 23 June 2015, 20 December 2015, and 26 August 2018, were selected based on their intensity (Dst ≤ -150 nT). Our analysis reveals that the primary drivers were interplanetary coronal mass ejections (ICMEs) and their preceding sheath regions. A key insight from this study is the diversity of the storm drivers; major storms were initiated not only by fast CMEs but also by slower CMEs with highly geo-effective magnetic field configurations. Specifically, the prolonged duration of a strong southward interplanetary magnetic field component (Bz) was identified as the crucial factor determining the magnitude of each storm, underscoring that forecasting models must prioritise the analysis of in-transit CME magnetic structure over initial kinematics to improve the prediction of severe storm impacts.